STUDI PEMBUATAN TEPUNG TERIPANG DARI BAHAN BAKU TERIPANG PASIR (HOLOTHURIA SCABRA) DENGAN PERLAKUAN PERBEDAAN KONSENTRASI GARAM DAN PERBEDAAN LAMA PEREBUSAN: (Study of Sea Cucumber Flour Production from Sea Cucumber (Holothuria scabra) with Treatment of Differences of Salt Concentration and Old Boiling Differences) - Rindam Latief; Amran Laga; Syamsul Alang (jurnal1, 2018)
Sea cucumbers have the prospect of being one of the most nutritious food sources because it has a complete nutritional content, including carbohydrates, some types of fatty acids and amino acids, some components of vitamins, sterols and some types of minerals. High nutritional content makes sea cucumber has potential as a food source of high grow factor. In addition, the content owned by sea cucumbers are also believed to function as antioxidants, antibacteria, antifungi, and anticoagulants. In Indonesia, sea cucumbers are still not widely used as food. This research studied how the effect of salt and boiling on the quality of content and physical acceptance of sea cucumber flour by the community. The production of sea cucumber by boiling and salting method is based on the habit of the people who boil or salt the sea cucumber at the time after the sea cucumber is captured. The salt concentration given in this study was 10%, 15% and 20%. While the temperatur treatment done by boiling sea cucumber for 10 minutes, 20 minutes and 30 minutes with a temperature of 70oC. The results obtained from this study showed that the nutrient content of sea cucumbers in boiling group has an average value of water content of 18.20%, ash content 19.61%, protein 51.17%, fat 3.76% and carbohydrates 7.27%. While the nutritional content of sea cucumber in salting group has an average value of water content 14.01%, ash 14.49%, 57.24%, fat 4.09% and carbohydrates 10.17%. The result of variance analysis showed that the sea cucumber produced from the boiling group and salting group did not significantly affect the nutrient content and the organoleptic parameters of sea cucumber. The conclusion obtained that the manufacture of sea cucumber either with the treatment of boiling or salting classified as having a fairly high nutritional content. So it is very potential to be developed more broadly on nutrient-rich food products.